Remuneration and Service Delivery in the Civil Services of Benue and Kwara States, Nigeria - Awotunde, Taiye Adewale; Ojo, Olawole (NIU Journal of Humanities, 2022)
The importance of remuneration in the sphere of public administration cannot be overemphasised. It is as a result of this that civil servants often clamour for better pay and improved welfare. The first major attempt at enhancing workers’ wages in Nigeria was made when the Udoji Commission reviewed the salaries of civil servants in 1974. The general objective of this study was to examine how remuneration affects service delivery in the civil service, with Benue and Kwara States as case study. The study examined the benefits and the challenges of remuneration in the civil service. The study also examined the issue of wage disparity among the federal and state government in Benue and Kwara States. The study anchored on Max-Weber’s bureaucratic theory. The methodology adopted for the study was survey research design. The population of the study was 1439, while the sample size was 313 based on Taro Yemani’s formula. The study adopted structured questionnaire for the collection of primary data. The study revealed that remuneration had significant effect on service delivery in Benue and Kwara States, F (1,304) = 53.077 (P < 0.05). Based on its findings, the study recommends that Benue and Kwara States should increase their revenue drives, in order to be able to augment with what they receive from the federation account. Keywords: Bureaucracy, civil service, motivation, remuneration, service delivery.